Clinical, haematological and biochemical observations following plasma and glycerin stored tendon allografting in equids - SAINI, N. S; MIRAKHUR, K K (The Indian Journal of Animal Sciences, 2013)
There is need of better tendon preservation techmques for feasIbility and healing of tendon after plasma stored and glycerin preserved tendon allografting in donkeys. Therefore, study was perfonned after tendon allografting of superficial digital flexor (SDF) tendon and surgically traumatizing deep digital flexor (DDF) tendon in 16 donkeys. In group 1 (n=8) plasma stored, and in group 2 (n=8) glycerin preserved tendon grafts were used. The grafted SDF and traumatized DDF tendons were encased in amniotic membrane. External coaptation applied for 8 weeks. Donkeys were observed at various stages up to 120 days. Animals of both the groups showed a significant rise of temperature, respiration and heart rates on first 2 operative days. Swelling reduced significantly on the fifth day and disappeared on the 42nd day in majority of the animals of group 1, whereas it persisted in 2 animals of group 2, which is also evident from the girth measurements of the operated limb. Girth measurements remained significantly more than normal up to 10 days (P< 0.01) and were nonnal by day 35 and showed no significant variation thereafter till the end of study period in the plasma stored tendon allografted animals (group 1). However, the girth measurements remained nlore and substantially higher in glycerin stored tendon allografted animals (group 2) till the end of study period. Contralateral limbs showed appreciable increase in the girth measurements up to 28 days in both the groups. Majority of the plasma stored allografted animals showed normal tendon gliding movements whereas glycelin stored tendon allografted animals (group 1) did not exhibit tendon gliding movements. Weight bearing on walk became normal in 33 ,6Â± 1,8 days and 36.4Â±3.4 days in groups 1 and 2 respectively. However, haematological and biochemical parameters showed no clinically significant change. It is concluded that plasma stored tendon allografts were clinically better than glycerin stored tendon allografts in equids.